Student recruitment in private nursing education institutions in South Africa - Lubbe, J. C. (University of the Free State, 2012)
Nurses form the cornerstone in achieving the millennium goals of the WHO with regard to health care. However, 57 countries worldwide are facing a severe health workforce crisis. Various solutions have been proposed to address the nursing staff shortage. One of the aspects that has been greatly neglected in South African research, however, is the initial recruitment of nursing students. Despite the critical importance of recruiting the best possible students for nursing education and training, very few private Nursing Education Institutions (NEIs) have a specific recruitment plan geared towards student recruitment. There is considerable evidence in the literature that some NEIs lack strategic planning for the recruitment of their students and that they do not always include all relevant stakeholders when initiating a recruitment drive. This study deals with the development of an action plan to aid with the recruitment of nursing students for private NEIs in South Africa. This study was structured around an adapted version of the process-planning model, as originally described by Zuber-Skerritt in 2002. Originally, a qualitative design with some quantitative enhancement was used. It was characterised by a descriptive, exploratory, and contextual focus. Three researcher-developed survey-questionnaires were used. During the last round of questionnaires, a quantitative approach, with qualitative enhancement was used. Final data analysis was done with the assistance of the SPSS software program. This study concluded with a generic action plan that was validated by experts in the field of student recruitment.

Verpleegkundiges vorm die hoeksteen om die WGO se millennium doelwitte vir gesondheidsorg te bereik. Wereldwyd is daar egter 57 lande wat tans 'n ernstige tekort aan gesondheidspersoneel ervaar. Verskeie voorstelle is al geopper om verpleegpersoneeltekorte aan te spreek. Een van die aspekte wat egter grotendeels in Suid-Afrikaanse navorsing oorgesien word, is die aanvanklike werwing van verpleegstudente. Afgesien van die kritieke belangrikheid om die bes moontlike studente vir verpleegopleiding te werf, het baie min private verpleegonderriginstansies 'n bepaalde werwingsplan om studente te werf. Daar is vo ldoende bewys in die literatuur dat sommige verpleegonderriginstansies 'n gebrek aan strategiese beplanning ten opsigte van hul studentewerwing het en dat hulle nie altyd al die betrokke belanghebbers by die instelling van 'n werwingsveldtog betrek nie. Hierdie studie handel oor die ontwikkeling van 'n aksieplan vir die werwing van verpleegstudente om opleiding by private verpleegonderriginstansies in Suid-Afrika te ondergaan. Die studie is saamgestel met die grondslag van 'n aangepaste weergawe van die prosesbeplanningsmodel wat oorspronklik in 2002 deur Zuber-Skerritt beskryf is. Aanvanklik is 'n kwalitatiewe ontwerp met behulp van kwantitatiewe bystand gebruik. Dit is deur 'n beskrywende, ondersoekende en konteksuele fokus gekenmerk. Orie vraelyste wat deur die navorser ontwikkel is, is aangewend. Tydens die laaste fase van die studie is kwantitatief gebaseerde vraelyste met behulp van kwalitatiewe ondersteuning aangewend. Die SPSS-sagtewareprogram is gebruik om die data behoorlik te analiseer. Die studie, wat deur kundiges op die vakgebied van studentewerwing bevestig is, het met 'n generiese aksieplan geeindig.
Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2012
Keywords: Action plan; Higher education/higher education and training; Nursing education/nursing education and training; Nursing Education Institutions (NEIs); Nurse; Private hospitals; Staff recruitment; Student recruitment; Shortage; South Africa (SA); South African Nursing Council (SANC); Training; Nursing -- Study and teaching -- South Africa; Nurses -- Recruiting -- South Africa